Fluvial and Eolian Sediment Mixing During Changing Climate Conditions Recorded in Holocene Andean Foreland Deposits From Argentina (31–33°S) - Capaldi, Tomas N.; George, Sarah W. M.; Hirtz, Jaime A.; Horton, Brian K.; Stockli, Daniel F. (Frontiers in Earth Science, 2019)
Continental drainage systems archive complex records of rock uplift, source area relief, precipitation, glaciation, and carbon cyclicity driven largely by tectonics and climate. Significant progress has been made in linking such external environmental forcings to the geomorphic expression of landscapes and the stratigraphic record of depositional basins in coastal and offshore areas. However, there are large uncertainties in the degree to which sediment dispersal processes can modify signals between the erosional sources and the depositional sinks. We investigate a Holocene sediment transfer zone with contrasting fluvial and eolian sediment transport mechanisms to understand how river and wind processes impact the propagation of environmental signals in continental-scale drainage systems. To quantify these processes, we employ sediment fingerprinting methods for unconsolidated sand samples (detrital zircon U-Pb geochronology), incorporate sediment mixing models, and correlate the findings with the regional geologic and geomorphic framework. Three contrasting source regions deliver sediment to the Andean foreland: volcanic rocks of the Frontal Cordillera, sedimentary rocks of the Precordillera, and metamorphic basement of the Sierras Pampeanas. Although all samples of Holocene eolian dunes accurately record sediment input from three fluvial source regions, spatial variations in U-Pb results are consistent with north-directed paleowinds, whereby river sediments from Frontal Cordillera sources are transported northward and progressively mixed with river sediments from Precordillera and Sierras Pampeanas sources. In contrast, samples of modern rivers show progressive southward (downstream) mixing along a large axial fluvial system. Sediment mixing induced by eolian transport and reworking of various sources is likely a critical, climate-modulated process in the propagation of environmental signals, potentially involving the aliasing of tectonic signals, local storage and recycling of synorogenic river sediment, and cyclical patterns of sediment starvation and delivery to distal zones of accumulation.